Cinderella’s Transformation - Linda T. Parsons (Study and Scrutiny)
Cinderella’s story endures through countless adaptations. In this study, I analyzed the tropes of the patiently suffering heroine, the cruel stepmother, magical help, beauty as female currency, and being chosen by the prince in Cendrillon (Perrault, 1697), Mechanica (Cornwell, 2015), and Cinder (Meyer, 2012). The (re)visions deconstruct binary gender roles through heroines who liberate themselves from their servitude, prioritize independence over marriage, and experience supportive female relationships. The portrayals of the cruel stepmothers disrupt the trope of powerful women as inherently evil, and the storylines critique the injustices of Othering. These (re)visions reflect contemporary discourses that expand expressions of femininity.